1986
DOI: 10.1002/eji.1830160704
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐α/β enhances the expression of Ly‐6 antigens on T cells in vivo and in vitro

Abstract: Interferons (IFN) have been shown to modulate the expression of a number of cell surface antigens on macrophages and lymphocytes. Because such phenotypic alterations may be involved in the functional effects of IFN, it appears important to characterize further these alterations. In the present work, we evaluated the response to IFN of Ly-6-encoded molecules on murine T cells. Two types of Ly-6 antigens, Ly-6A and Ly-6C, normally present on minor subsets of mature T cells were studied. It was found that in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 27 publications
8
47
1
Order By: Relevance
“…The simplest explanation for the dramatic reduction in Sca-1 Ϫ/Ϫ HSCrepopulating ability between primary and secondary BM transplantations is that Sca-1 plays an important role in HSC self-renewal, at least in response to hematologic stress caused by lethal irradiation and transplantation. This explanation is consistent with the regulation of Sca-1 by interferons 25,26 and tumor necrosis factor-␣ (TNF-␣), 27 which are known to be induced in response to (1) cellular stress; (2) Under homeostatic conditions (ie, Sca-1-null mice), Sca-1 is not required for stem cell maintenance, which is consistent with a role for Sca-1 as a coregulator of cell signaling; in this case, however, a coregulator of the signals that mediate stem cell self-renewal. A postulated molecular role of Sca-1 and other GPI-anchored proteins is to modulate signaling by Src family kinases, receptor tyrosine kinases, and other signaling molecules in lipid rafts.…”
Section: Discussionsupporting
confidence: 74%
“…The simplest explanation for the dramatic reduction in Sca-1 Ϫ/Ϫ HSCrepopulating ability between primary and secondary BM transplantations is that Sca-1 plays an important role in HSC self-renewal, at least in response to hematologic stress caused by lethal irradiation and transplantation. This explanation is consistent with the regulation of Sca-1 by interferons 25,26 and tumor necrosis factor-␣ (TNF-␣), 27 which are known to be induced in response to (1) cellular stress; (2) Under homeostatic conditions (ie, Sca-1-null mice), Sca-1 is not required for stem cell maintenance, which is consistent with a role for Sca-1 as a coregulator of cell signaling; in this case, however, a coregulator of the signals that mediate stem cell self-renewal. A postulated molecular role of Sca-1 and other GPI-anchored proteins is to modulate signaling by Src family kinases, receptor tyrosine kinases, and other signaling molecules in lipid rafts.…”
Section: Discussionsupporting
confidence: 74%
“…Although we cannot exclude that the loss of naive cells in part reflects interconversion of naive to memory T cells, triggered perhaps by pI/pC-induced IFN, we consider it unlikely that this represents a major effect. Indeed, we have not observed a significant change in the proportions of naive versus memory TCR ϩ cells 10 days after pI/pC injection, and earlier work has shown that IFN-induced up-regulation of CD44 and Ly6C on naive T cells is transitory and not accompanied by cellular proliferation (30,31).…”
Section: Discussioncontrasting
confidence: 39%
“…6). These data suggest that although IFN-I has been shown to induce Ly6C expression (24), the Ly6C high phenotype of the immature monocyte population in naive or TMPD-treated mice was not dependent on IFN-I signaling.…”
Section: Surface Expression Of Ly6c On Monocytes Is Not Ifn-i-dependentmentioning
confidence: 79%
“…Because Ly6C is an IFN-inducible gene (24), it is possible that IFN-I production triggered by TMPD treatment contributes to the Ly6C high monocyte phenotype. To address this issue, we analyzed monocyte subsets in IFNAR Ϫ/Ϫ mice.…”
Section: Surface Expression Of Ly6c On Monocytes Is Not Ifn-i-dependentmentioning
confidence: 99%